PENERAPAN PENDEKATAN PROBLEM BASED LEARNING BERBASIS SCAFFOLDING UNTUK MENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Ariyanti, Ariyanti (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
The research aims to improve students' communication mathematis skills through the provision of an experiment that is the application of a problem based learning approach based scaffolding in elementary school students. The research design uses Quasi Experimental design with pre-posttest design. This research was conducted in 6 classes from 3 different elementary schools in Bandung with the number of research subjects consisting of 2 classes, namely the experimental class and the control class. Experimental class getting learning with problem based learning approach based scaffolding and control class getting conventional learning. The number of subjects was 191 students with details: in the experimental class were 89 students and the control class were 102 students, each of whom was spread over 3 different elementary schools. The results showed that there was an increase in mathematical communication skills after PBL-based scaffolding compared with students taught by conventional methods, where the estimated marginal mean value in the experimental group was higher than in the control group, which was 0.318> 0.124.